Sidewalk Features as a Place for Social Interaction in Streetscape Case study: Al-Nasr Street in Damascus - عبسي, زهراء (Latakia University Journal -Engineering Sciences Series, 2022)
Over past three decades number of studies have been conducted in the field of relationship between built environment with human and social activities of various disciplines. In the field of urban study, the main objective of these studies was to set guidelines for urban planning, urban design and space analysis because misunderstanding people's needs can be an obstacle for designers to create a better urban place in social life which can be stimulated. The research reviews each of the features of sidewalk as an important place and its elements in streetscape which related to pedestrian movement and activities that affected by the elements of built environment in it. Research focus on street space as a place then link within street network, pavement plays this important role to direct pedestrian movement and their interaction. Function of streets as place and the most important element enhances and develops social relations in it. Then present a group of international experiences, leading to the development of a set of results and recommendations aimed to raise the efficiency of important streets within cities in supporting their role as a basic nucleus in developing social relations and enhancing belonging to the place.